2013
DOI: 10.1007/s10096-013-1839-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite-primed PCR and random primer amplification polymorphic DNA for the identification and epidemiology of dermatophytes

Abstract: This study demonstrates the capacity of the one-step polymerase chain reaction (PCR) fingerprinting method using the microsatellite primers (GACA)4 or (GTG)5 (MSP-PCR) to identify six of the most frequent dermatophyte species causing cutaneous mycosis. PCR with (GACA)4 was a suitable method to recognise Microsporum canis, Microsporum gypseum, Trichophyton rubrum and Trichophyton interdigitale among 82 Argentinian clinical isolates, producing the most simple and reproducible band profiles. In contrast, the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
13
1
2
Order By: Relevance
“…39,52 This epidemiological pattern of clustered cases and high incidence in a short period of time is better known for viral 53 and bacterial pathogens; 54 such events caused by fungi are very rare in humans and are mainly limited to dermatophytes. 55 The emergence of fungal pathogens in other animals is mostly related to a recent introduction or shift in host, as in the case of white-nose syndrome in bats caused by Geomyces destructans , 56 lethargic crab disease by Exophiala cancerae 57 and the devastation of amphibian populations caused by the chytridiomycete Batrachochytrium dendrobatidis . 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…39,52 This epidemiological pattern of clustered cases and high incidence in a short period of time is better known for viral 53 and bacterial pathogens; 54 such events caused by fungi are very rare in humans and are mainly limited to dermatophytes. 55 The emergence of fungal pathogens in other animals is mostly related to a recent introduction or shift in host, as in the case of white-nose syndrome in bats caused by Geomyces destructans , 56 lethargic crab disease by Exophiala cancerae 57 and the devastation of amphibian populations caused by the chytridiomycete Batrachochytrium dendrobatidis . 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…RAPD and ISSR-PCR methods have frequently been used for phylogenetic analysis and identification of dermatophytes (Kim et al, 1999(Kim et al, , 2001Cano et al, 2005;Leibner-Ciszak et al, 2010). Spesso et al (2013) demonstrated that the detection of intra-species polymorphisms in isolates of M. canis by RAPD-PCR may be applied in future molecular epidemiological studies in order to identify endemic strains, the route of infection in an outbreak and the coexistence of different strains in a single infection. In contrast to that reported and using the same method, Leibner-Ciszak et al (2010) were not able to detect genetic variations in 13 clinical isolates of M. canis.…”
Section: T Mentagrophytes (E)mentioning
confidence: 99%
“…However, outside factors such as temperature variation, medium and chemotherapy, can greatly influence the phenotypic characteristic and consequently can make the identification more difficult (Weitzman and Summerbell, 1995;Faggi et al, 2001;Kanbe, 2008;De Baere et al, 2010). Recently, molecular marker approaches, such as nested-polymerase chain reaction (PCR) (Verrier et al, 2013), random amplified polymorphic DNA (RAPD)-PCR (Kim et al, 2001;Baeza et al, 2006;Leibner-Ciszak et al, 2010;Dobrowolska et al, 2011;Spesso et al, 2013), inter-simple sequence repeat (ISSR)-PCR (Cano et al, 2005;Khosrav et al, 2012), PCR-restriction fragment length polymorphism (RFLP) (Yang et al, 2008;RezaeiMatehkolaei et al, 2012;Samuel et al, 2013), real time PCR (Bergmans et al, 2010) and multiplex PCR assay (Arabatzis et al, 2007;Kim et al, 2011) and others have been adapted for detection of dermatophytes from clinical specimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods can be used to detect the pathogenic dermatophytes from the clinical samples with remarkable reliability. However, these methods are complicated and require pure DNA samples in large quantity, and thus are not suitable for rapid identification and examination of large groups of clinical samples [Faggi et al, 2001;Spesso et al, 2013].…”
Section: Introductionmentioning
confidence: 99%